2010
DOI: 10.1111/j.1365-3040.2009.02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis ofTaDi19A, a salt-responsive gene in wheat

Abstract: A salinity stress upregulated expressed sequence tag (EST) was selected from a suppression subtractive hybridization cDNA library, constructed from the salinity-tolerant wheat cultivar Shanrong No. 3. Sequence analysis showed that the corresponding gene (named TaDi19A) belonged to the Di19 family. TaDi19A was constitutively expressed in both the root and leaf of wheat seedlings grown under nonstressed conditions, but was substantially up-regulated by the imposition of stress (salinity, osmotic stress and cold)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 74 publications
1
31
0
1
Order By: Relevance
“…Recently, a study indicated that TaDi19A is up-regulated in wheat seedlings by abiotic stresses (such as salinity, osmotic stress and cold) and stress-related hormones (such as ABA and ethylene). Overexpression of TaDi19A in Arabidopsis increases the sensitivity of transgenic plants to NaCl, mannitol and ABA during seed germination (Li et al 2010). However, GhDi19-1/-2 transgenic plants responded to mannitol in a same manner as wild type, although both Di19 genes were induced by drought stress in cotton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study indicated that TaDi19A is up-regulated in wheat seedlings by abiotic stresses (such as salinity, osmotic stress and cold) and stress-related hormones (such as ABA and ethylene). Overexpression of TaDi19A in Arabidopsis increases the sensitivity of transgenic plants to NaCl, mannitol and ABA during seed germination (Li et al 2010). However, GhDi19-1/-2 transgenic plants responded to mannitol in a same manner as wild type, although both Di19 genes were induced by drought stress in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, AtDi19-7 has been implicated in regulating light signaling and responses, but its expression is not changed in response to abiotic stress treatments (Kang et al 2005), suggesting that AtDi19 proteins may functionally participate in different signaling pathways. A more recent study revealed that wheat Di19A may play a role in plant responding to abiotic stress (Li et al 2010). Besides, previous studies showed that some of the other zinc-finger proteins are involved in abiotic stress signaling in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…These plants showed an increase in the number of ERD15 transcripts relative to control plants [44]. Transgenic wheat plants over-expressing TaDi19A, a gene responsive to salinity in wheat, exhibited increased expression of ERD15 [45]. In contrast to these findings, Arabidopsis plants over-expressing ERD15 demonstrated susceptibility to drought and freezing [35].…”
Section: The Early Responsive To Dehydration (Erd) Genes and Their Fumentioning
confidence: 88%
“…Nuclear localization is an integral part of abiotic stress response. Many stress-associated proteins, like some TFs (bZIP, DREB, MYC/MYB, NAC, C 2 H 2 zinc finger protein Msn2P), some kinase gene and a number of functional proteins belong to a subset of cellular proteins that localize to the nucleus [11], [12], [53], [54], [55], [56], [57], [58], [59]. Genomic organization study showed that SbSI-2 is an intronless gene (Fig.…”
Section: Discussionmentioning
confidence: 99%